Pengaruh Green Accounting dan Corporate Social Responsibility terhadap Tax Avoidance dengan Firm Size sebagai Variabel Moderasi - Nabilah, Dwi Uthari; Rusdi, Rusdi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
In recent years, environmental sustainability and social responsibility have become increasingly important in corporate financial strategies, especially in emerging markets like Indonesia. Companies are expected not only to pursue profitability but also to engage in sustainable practices such as green accounting and corporate social responsibility (CSR). However, concerns remain regarding whether such practices are used to obscure unethical actions like tax avoidance. This study investigates the effect of green accounting and CSR on tax avoidance, with firm size as a moderating variable, in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2023. Using purposive sampling, 10 companies were selected from a population of 130, generating 60 panel data samples over six years. The study employed panel data regression analysis using EViews 12 and Microsoft Excel 2019. The findings reveal that green accounting and CSR jointly influence tax avoidance. However, individually, neither green accounting nor CSR significantly affect tax avoidance. Additionally, firm size does not moderate the relationship between green accounting and tax avoidance or between CSR and tax avoidance.